Capture My Head: A Convenient and Accessible Approach Combining 3D Shape Reconstruction and Size Measurement from 2D Images for Headwear Design. (June 2023) - Zhang, Jie; Luximon, Yan; Wan, Jingyi; Li, Ping
Abstract: 3D physical head capture has many applications for headwear and facewear design. However, the existing methods, usually using commercial scanners, are not cheap or convenient, thereby limiting their popularity and accessibility. Therefore, we propose a convenient and cheap approach to 3D head capture by combining shape reconstruction and size measurement from images, using only two printed templates and a mobile phone camera. For the shape reconstruction process, we presented a 3D morphable model (3DMM)-based method to reconstruct the 3D shape from an arbitrary number of face images. Using this method, two powerful 3DMMs of head shapes and textures are constructed, and a novel facial landmark-to-edge loss based on corrected landmarks is developed. For size measurement, we proposed a coarse-to-fine circular object diameter measurement method, used to measure a circular label or object (e.g., a coin) placed on the forehead. The experimental results confirm a cost-effective number and size of input face images for our method. Furthermore, the method comparisons demonstrate that our head reconstruction methods have superior accuracy to state-of-the-art methods. Our convenient approach can be applied to the ergonomic design field, as well as individual customizations, virtual try-ons, and size selection for head-related products. Highlights: To the best of our knowledge, it is the first attempt to develop a convenient and cheap approach to 3D head (shape and size) capture. We proposed a more accurate 3DMM-based 3D head shape reconstruction method with a novel landmark-to-edge loss. We determined a cost-effective number and size of input face images for 3D head shape reconstruction. We developed a more stable and accessible coarse-to-fine circular object diameter measurement method. We greatly extended the applications of 3D head reconstructions from 2D images to facewear/headwear design.